(untitled) (Research, Society and Development, 2022)
The preparation and administration of medications are steps in the medication system, being the last part of the process that precedes the patient. A system composed of several inputs and processes and with the participation of mid-level and higher education professionals, physicians, nurses, pharmacists and pharmacy and nursing technicians. Among the drug liability, there is a group called High-Surveillance Drugs or Potentially Dangerous Medicines, so through pharmacovigilance require more rigorous care, due to their composition and the capacity for death they have, when administered in a way erroneous. Therefore, this work aims to demonstrate the importance of the preparation and administration of type medications and its interface with patient safety. A narrative review was carried out based on a search in the Latin American Literature in Health Sciences (LILACS), BIREME and Scientific Electronic Library Online (SciELO) electronic databases, with a time frame from 2010 to 2021. After applying the criteria of inclusion and exclusion, and complete reading of the texts, 10 works were selected. The survey demonstrated the repetition of errors with AVM involving medications: heparin, fentanyl, midazolam, nalbuphine, pancuronium, dopamine, potassium chloride, tramadol, epinephrine, pethidine, morphine and also with anesthetics and electrolytes. The research demonstrated the fragility of the data recorded in the articles found, not categorizing risks in larger populations, being incipient and insignificant for a reality of the scope of the country and/or by regionality.